Theology as a Science - Gerhard Ludwig Müller (Wrocławski Przegląd Teologiczny)
The vantage point of the article is to show the formation process of the concept and objective of Christian theology from the historic perspective. The concept of theology itself stems from its function within the Church – it is the acceptance and execution of the Revelation. Theology is the task of the Church as a whole, as it leads to getting to know God and the ultimate objective of man. Through the establishment of the relation between reason and faith, theology becomes for one a place of searching for answers to fundamental questions concerning the reason for one’s existence. As theology has its sources in the self-revelation of God in His Word, getting to know God is complete on the personal plane in the love for Him. Theology is not a science in the full extent of the concept, as it is executed by reason, and through this, it participates in the cognition of all reality. Today it seems to be a proposition of a fundamental anthropological science, in light of the distribution of specialities of special sciences at universities, as it deals with fundamental questions. On the other hand, theology has in its core the spreading of the Gospel, and this remains its task as a science in the university realm.